2018
DOI: 10.1016/j.envint.2018.05.035
|View full text |Cite
|
Sign up to set email alerts
|

Estimated health benefits of exhaust free transport in the city of Malmö, Southern Sweden

Abstract: Air pollution is responsible for one in eight premature deaths worldwide, and thereby a major threat to human health. Health impact assessments of hypothetic changes in air pollution concentrations can be used as a mean of assessing the health impacts of policy, plans and projects, and support decision-makers in choices to prevent disease. The aim of this study was to estimate health impacts attributable to a hypothetical decrease in air pollution concentrations in the city of Malmö in Southern Sweden correspo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 48 publications
2
20
0
Order By: Relevance
“…Moreover, it is well known that traffic-related air pollution (such as NO x , NO 2 , ultra-fine particles) can trigger asthma symptoms in human beings [15]. Current Swedish publication suggests that the implementation of exhaust-free transport would lead to a reduction in NO 2 emission and in consequence to a significant decrease (by 10%) of bronchitis in asthmatic children, even in one of the cleanest region of Europe [16]. Similarly, the results of epidemiological studies in Japan revealed that traffic-related air pollution was associated with the persistence of respiratory disorders such as asthmatic symptoms in preschool children.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, it is well known that traffic-related air pollution (such as NO x , NO 2 , ultra-fine particles) can trigger asthma symptoms in human beings [15]. Current Swedish publication suggests that the implementation of exhaust-free transport would lead to a reduction in NO 2 emission and in consequence to a significant decrease (by 10%) of bronchitis in asthmatic children, even in one of the cleanest region of Europe [16]. Similarly, the results of epidemiological studies in Japan revealed that traffic-related air pollution was associated with the persistence of respiratory disorders such as asthmatic symptoms in preschool children.…”
Section: Discussionmentioning
confidence: 99%
“…One study estimated that 11% of term low birth weight cases would be avoided if the PM2.5 concentration was reduced by 5 µg/m 3 (58). Another suggests that 11% of all PE cases were attributable to exhaust emissions in Malmö, Sweden (79). Indeed, the PM2.5 used in our present study was collected in real-life conditions in Malmö, Sweden in order to mimic the actual exposure pregnant women face in an urban setting.…”
Section: Public Health Impactmentioning
confidence: 99%
“…One of our findings was that up to 4% of all premature deaths could be prevented if all petrol-and diesel-powered vehicles were banned from Malmö [13]. The results of the HIA were published in Malmqvist et al [13] and spread in popular forms in an information folder produced in collaboration between the research team and the Environmental Office [14] and a Youtube video, entitled "The health effect of air pollution from traffic" [15]. The qualitative part of the project presented here focuses on how civil servants, working with air pollution and noise abatement in Malmö municipality, access, process, and apply research results and other sources of information in their everyday work.…”
Section: Introductionmentioning
confidence: 80%
“…The HIA also estimated the societal costs of pollution and of lowered costs when mitigating hazards. One of our findings was that up to 4% of all premature deaths could be prevented if all petrol-and diesel-powered vehicles were banned from Malmö [13]. The results of the HIA were published in Malmqvist et al [13] and spread in popular forms in an information folder produced in collaboration between the research team and the Environmental Office [14] and a Youtube video, entitled "The health effect of air pollution from traffic" [15].…”
Section: Introductionmentioning
confidence: 99%